Penerapan Sistem General Rules dan Special Rules dalam Undang-Undang Khusus - Dianita Rahma Nugraheni; Pujiyono Pujiyono (JURNAL BELO, 2022)
The essence of criminal law reform is the renewal of intellectual conceptions or philosophical activities. The implementation of the integrated system between "general rules" and "special rules" in the substantive criminal system in Indonesia is not yet ideal. Understanding of the criminal system that should be based on the main provisions, namely the Criminal Code/WvS tends to be ignored. Such conditions will be more complicated when the reform of the Criminal Code is drafted and is not handled intelligently and wisely by the legislature in its formulation stage. The research conducted is normative legal research or literature study. Learning about the criminal system in the main provisions of the Criminal Code must be integrated with the criminal system of the Draft Criminal Code in the criminal law curriculum in higher legal education. This is intended so that students' understanding can also develop so that when the Criminal Code Bill is passed it will be easy to implement it. Based on the statement above, this paper was prepared with the hope of providing an initial overview for law students and law enforcement officers to be able to determine their attitudes and prepare their competencies.